(untitled) (Psychology Travelogs, 2024)
The article examines various aspects of anxiety, including its definition, manifestations, and the factors that trigger it. Anxiety is defined as an emotional state accompanied by negative feelings and nervous system activity, which can arise in response to both real and imagined threats. It has two main functions: protective and motivational, and can manifest as situational or personal. Anxiety can be both overt and hidden, depending on the level of expression and individual characteristics of the person. The article pays particular attention to the anxiety experienced by parents of children with special educational needs. It explores specific manifestations of anxiety in these parents, such as overprotection, excessive concern, fears about the child’s future, and psychological stress arising from the constant challenges and demands of daily life. The impact of these manifestations on the emotional and psychological state of parents is analyzed, especially in crisis situations. The article also investigates the impact of war on the level of anxiety in parents. War exacerbates anxiety due to socio-economic difficulties, instability, fears for the child’s future, and the need for constant support. Various strategies for managing anxiety used by parents are examined, and the importance of psychological support in mitigating negative consequences is emphasized. The role of psychological support in alleviating stress and anxiety experienced by parents and its impact on the overall family situation in times of war are discussed. Further research should focus on developing effective psychological support programs to help reduce anxiety in parents of children with special educational needs and enhance their ability to adapt in wartime conditions.